Educational Intervention “Open Conversation and Reflection” to Enhance Person-Centeredness in Acute Geriatric Wards: A Qualitative Study of Consequences and Processes - Karen Versluys; Sarah Janssens; Mieke Grypdonck; Let Dillen; Nele Van Den Noortgate; Linus Vanlaere; Ruth Piers (Palliative Medicine Reports)
Background: Person-centered supportive care for older persons with acute illness is much needed but not easily achieved. Aims of the Study: To uncover processes and consequences of an educational intervention in acute geriatric wards intended as an exposure experience. Design: General inductive qualitative analysis was conducted on data from a four-step intervention: group coaching, an open conversation with a patient and family member (PT/FM), reflection on transcribed conversations with co-participant, and group peer reflection. Methods: Twelve participants engaged in the intervention. Transcripts from paired reflection sessions and peer reflections were analyzed using general inductive qualitative analysis. Results: The exposure experience of the participants involved three major processes: (1) fear before the conversation, (2) presence during the conversation, and (3) responsiveness after the conversation. Each process entailed several substeps. Not only the open conversation but also the whole process of reflection with a co-participant after reading the transcript and the peer-reflection sessions seem to be needed to realize the exposure experience. Conclusions: Through the educational intervention “open conversation and reflection,” participants experienced that connecting with PT/FM and listening to what is important to them are essential to realize person-centered care. Thus, pending further studies, the educational intervention can be considered promising to enhance person-centeredness in older people’s care.